Absolute Eosinophil Count as a Clinical Marker for COPD Assesment - Rehman, Atta Ur; Muhammad Imran; Muhammad Arif Sadiq; Muhammad Wasiullah Khan; Attia Khaliq; Bilal Rasheed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the predictive value of absolute eosinophil count as a clinical biomarker for acute exacerbations in COPD patients and their clinical outcomes.Study design: Prospective Observational StudyPlace and duration of Study: Pakistan Emirates Military Hospital Rawalpindi Pakistan from May to Dec 2023.Methodology: A total of 300 COPD patients fulfilling inclusion criteria were enrolled in the study. After detailed history and examination and assessment of severity of COPD, a 5ml blood venous blood was drawn and sent for CBC and absolute eosinophil count. The patients were divided into Group A and B based on absolute eosinophil count of less or more than 300/ul. They were admitted to indoor patient department depending upon severity of the disease into high dependency unit or pulmonology ward. The patients were followed up till discharge from the hospital or death in the hospital.Results: Out of total 300 patients, 122(40.7%) were categorized into Group A and 178(59.3%) were categorized into Group B based on absolute eosinophil count of less or more than 300/ul respectively. Group B patients were found to have statistically significant (p300/ul were found to be having more severe disease, acute exacerbation, admissions to HDU, mechanical ventilation requirement and mortality.